CARDIOTOXICITY OF CHRONIC SUNITINIB TREATMENT IN NORMOTENSIVE AND SPONTANEOUSLY HYPERTENSIVE RATS. (21st November 2014) - Nemeckova, I; Lencova, O; Jirkovsky, E; Adamcova, M; Nachtigal, P; Sterba, M
Abstract : Aims: Sunitinib is a modern multi-targeted tyrosine kinase inhibitor, which showed great promise in the treatment of human cancer. However, its chronic use may be associated with cardiotoxicity, which is poorly understood. Hence, the aim of the present study was to investigate potential cardiotoxicity of chronic sunitinib treatment in normotensive and spontaneously hypertensive rats. Methods: Spontaneously hypertensive rats (SHR) and their normotensive littermates (Wistar Kyoto, WKY) were used in the study (n=32). Sunitinib (10 mg/kg) was administered daily for 8 weeks and after a wash out period (5 days) a re-challenge for 2 and 8 weeks followed in WKY and SHR rats, respectively. Results: Sunitinib treatment induced a significant left ventricular (LV) dysfunction and decline in heart rate. This was accompanied by increased LV BNP expression, increased BNP plasma concentrations and increased lung to body weight ratio. Remarkably, no such change was found in SHR despite significantly longer duration of treatment. Moreover, sunitinib-induced cardiac dysfunction in WKY was accompanied by marked expression of numerous hypoxia-regulated genes and inflammatory molecules. Conclusions: In conclusion, our findings show different propensity of WKY and SHR animals towards sunitinib cardiotoxicity development and suggest an important role of hypoxic signaling in this process. Furthermore, possible involvement of "hibernating myocardium" in sunitinib-induced cardiac dysfunction deserves further study, particularly with respect to recently reported impairment of cardiac microvasculature. The publication is co-financed by the European Social Fund and the state budget of the Czech Republic, project no. CZ.1.07/2.3.00/30.0061. This work was supported by project UNCE 33/2012.